Kaasstengels: Modified Cookies Made from Durian Seed Flour - Zuhro, Helsa Hotima Ratu (Gastronary, 2024)
The objective of this study is to determine the processing method of kaasstengels and to analyze the preference level of panelists for kaasstengels made with durian seed flour. The population used in this study consists of the members of the Culinary UKM at STP AMPTA Yogyakarta in 2023, totaling 20 people. The sampling method used in this study is the saturated sampling method, which means that the sample in this study is the entire 2023 membership of the Culinary UKM, totaling 20 people. The analytical techniques used in this study include a hedonic test and an organoleptic test approach, while the analysis was performed using the one-sample t-test. The results of the study indicate that the responses from the three experts agreed that, from various aspects, the best results for making kaasstengels with durian seed flour are obtained with a 50:50 ratio between durian seed flour and wheat flour. Through data analysis using the One Sample T-Test method, it was found that the aspects of aroma, taste, and appearance had t-values smaller than the t-table values, −4.8951 < 1.729, -7.6661 < 1.729, 0.8600 < 1.729, which means that these three aspects were not liked by the panelists. On the other hand, through data analysis using the One Sample T-Test method, it was found that the texture aspect had a t-value greater than the t-table value, 7.1554 > 1.729, indicating that the texture aspect was liked by the panelists.